KEARIFAN LOKAL, KUALITAS SUMBER DAYA MANUSIA DAN DAYA TARIK WISATA UNTUK KEBERLANJUTAN DESTINASI DESA - Muh Taufik; Ahmad AB; Nur Salam (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractThe prolonged Covid-19 pandemic has weakened the economy in Indonesia. One of the biggest impacts was also felt in the tourism sector where all destination areas were closed due to this disaster which had an impact on the development of the creative economy in the destination area. The aim of this study is local wisdom, quality of human resources managers and destination attractions for village destination sustainability in the midst of pandemic Covid-19. This study is a quantitative approach using questionnaires as a method of data collection, where the number of samples used as many as 140 people with accidental sampling techniques, the analysis method in this study using the model of structural equations with the application of Amos. The findings of this study show that local wisdom on the attractiveness of destinations has a positive and significant influence, the quality of human resources has a positive and significant influence on tourist attraction, tourist attraction has a positive and significant influence in influencing the sustainability of destinations, local wisdom has an insignificant influence in encouraging destination sustainability,  The quality of human resources to the sustainability of the destination shows a positive and significant direction, and indirectly shows the attractiveness of tourism has an insignificant effect as a mediation variable for local wisdom on the sustainability of the destination. This study suggests the need to improve the quality of human resources who are able to see tourism development trends and use local wisdom with several new innovations so that they can attract tourists. Keywords: local wisdom, quality of human resources, destination attractions, sustainability of the destination